Pengaruh Kompetensi, Team Work dan Budaya Organisasi Terhadap Kinerja Melalui Motivasi Pada Pusat Penelitian Kelapa Sawit (PPKS) Medan - Janah, Aulia Cahyaningrum; Siregar, Budi Alamsyah; Elanda, Yochi (CV. Rayyan Dwi Bharata, 2025)
The aim of this research is to examine the influence of competence, team work and organizational culture on employee performance through motivation at the Medan Palm Oil Research Center (PPKS). This type of research is quantitative. The population at the Medan Palm Oil Research Center is 451 employees. The sample taken in this research was 82 employees. This research collects data through distributing questionnaires. Data analysis methods are used in research using instrument tests (validity and reliability tests), classical assumption tests (normality tests, multicollinearity tests, and heteroscedasticity tests), hypothesis tests (t tests),path analysis tests. Based on the research results, it shows that there is a partial influence between competence on motivation, because tcount 9.285 ttable 1.990, there is a partial influence between team work on motivation, because tcount 11.726 ttable 1.990, there is a partial influence between organizational culture and motivation on motivation, because tcount 8.503 ttable 1.990, there is a partial influence between competence on employee performance, because tcount 8.765 ttable 1.990, there is a partial influence between teamwork on employee performance, because tcount 9.982 ttable 1.990, there is a partial influence of organizational culture on employee performance, because tcount 8.488 ttable 1.990, there is a partial influence of motivation on employee performance because tcount 8.659 ttable 1.990.